1993
DOI: 10.1002/1098-108x(199307)14:1<27::aid-eat2260140104>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eating disorders and other dietary/weight groups on measures of perceived control, assertiveness, self-esteem, and self-directed hostility

Abstract: Anorexic and bulimic patients were compared to obese dieters, nonobese dieters, and normal controls on measures of perceived control, assertiveness, self‐esteem, self‐directed hostility, and psychiatric caseness. The anorexic and bulimic groups both scored significantly differently in the expected direction from the other three groups on all measures. There were no significant differences between the anorexic and bulimic groups and in turn, no significant differences among the obese, nonobese dieters, and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
2
7

Year Published

1994
1994
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 9 publications
10
58
2
7
Order By: Relevance
“…In an attempt to correct the methodological weaknesses suggested in the Williams et al (1990) study, a similar investigation (Williams et al, 1993) was designed to compare anorexics and bulimics to obese dieters, nonobese dieters, and normal controls on many of the same variables (e.g., self-directed hostility, assertiveness, and locus of control). Williams et al (1993) also examined these groups in terms of self-esteem explaining that the results in the previous investigation suggested that eating disordered women would report lower self-esteem.…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to correct the methodological weaknesses suggested in the Williams et al (1990) study, a similar investigation (Williams et al, 1993) was designed to compare anorexics and bulimics to obese dieters, nonobese dieters, and normal controls on many of the same variables (e.g., self-directed hostility, assertiveness, and locus of control). Williams et al (1993) also examined these groups in terms of self-esteem explaining that the results in the previous investigation suggested that eating disordered women would report lower self-esteem.…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 99%
“…Williams et al (1993) also examined these groups in terms of self-esteem explaining that the results in the previous investigation suggested that eating disordered women would report lower self-esteem. Williams et al Prior research also has focused on personalityvariables present during the course of the disorders; therefore, it is not clear if these factors reflect underlying personality structures or merely symptoms related to the disorders.…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they report lower global selfesteem than women without disorders (Attie & Brooks-Gunn, 1989;Huon & Brown, 1984;Williams, et al, 1993). However, with results similar to body-size overestimation, other populations of women have also been found to have high levels of body dissatisfaction and low self-esteem (Rodin, Silberstein, & Streigel-Moore, 1985).…”
Section: Self-esteem Disturbancesmentioning
confidence: 99%
“…Participants vocalized a sense of needing to compensate in the body image domain when the academic domain felt threatened. This finding is consistent with eating disorder research that suggests that individuals with eating disorders display elevated levels of perceived control and low-self esteem (Williams et al, 1993). The idea of needing to compensate stemming from a core question of comparison and status with other people can be conceptualized as both an internalized and externalized presentational concern.…”
Section: Academic Stressmentioning
confidence: 99%